1979
DOI: 10.1136/gut.20.3.249
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial gastric function in pancreatic insufficiency.

Abstract: SUMMARY Abnormalities in postprandial gastric function could contribute to the maldigestion of pancreatic insufficiency. To measure simultaneously postprandial gastric secretion and emptying and correlate these measurements with intraluminal duodenal changes, we performed intestinal intubation and duodenal perfusion during feeding of a solid-liquid test meal in 10 healthy controls and 10 patients with documented pancreatic insufficiency before and after replacement therapy. In pancreatic insufficiency, intradu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…On the other hand, ulcer has been re ported to be common after pancreatectomy [7] which impairs the exocrine pancreatic function. Moreover, an increased pentagastrin acid output has been observed in chronic pancreatitis with steatorrhea [20] even if Re gan et al [17] found a slight reduction in the postprandial acid output. The acidic duode num could be considered a producing or en hancing factor of DU formation in patients with pancreatic insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, ulcer has been re ported to be common after pancreatectomy [7] which impairs the exocrine pancreatic function. Moreover, an increased pentagastrin acid output has been observed in chronic pancreatitis with steatorrhea [20] even if Re gan et al [17] found a slight reduction in the postprandial acid output. The acidic duode num could be considered a producing or en hancing factor of DU formation in patients with pancreatic insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…T here were two pscudocysts in the body and ( 14, I 5). This hypcrgastrincmia may be secondary to chronirnll y reduced gastric acid secretion ( 14). On the other hand, a more recent study indicated that patients with severe pancrcmic insufficiency frequently have had gawic acid hypcrsccretion ( 15).…”
Section: Case Presentationmentioning
confidence: 99%
“…In chronic pan creatitis. it normally takes several years for severe exocrine pancreatic insufficiency to de velop, but lipase secretion is more rapidly impaired than the secretion of proteolytic en zymes [17], because lipase in the intestinal lumen is more fragile than the other enzymes. Lipase is easily inactivated by acidic pH and digested by proteolytic enzymes.…”
Section: Association Of Altered Gastrointestinal Functions With Distumentioning
confidence: 99%